Catalytic upgrading of soybean oil methyl esters by partial hydrogenation using Pd catalysts. (1st January 2016) - Thunyaratchatanon, Chachchaya; Luengnaruemitchai, Apanee; Chollacoop, Nuwong; Yoshimura, Yuji
Abstract: Fatty acid methyl esters derived from soybean oil were partially hydrogenated over three types of catalysts-Pd, Pt, and Ni-supported on SiO2 . The effect of the sulfur compounds on catalytic activity of the three noble metals was investigated. In both hydrogenated biodiesel with and without additional sulfur compounds, the turnover frequency (TOF) for partial hydrogenation over Pd/SiO2 was greater than that over the Pt/SiO2 and Ni/SiO2 catalysts. On the other hand, Pt/SiO2 exhibited the most sulfur tolerance. Partially hydrogenated biodiesel were found to have better oxidative stability compared to non-hydrogenated biodiesel.